2011
DOI: 10.1158/0008-5472.can-10-2345
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs miR-199a-5p and -3p Target the Brm Subunit of SWI/SNF to Generate a Double-Negative Feedback Loop in a Variety of Human Cancers

Abstract: The chromatin remodeling complex SWI/SNF is an important epigenetic regulator that includes one Brm or BRG1 molecule as catalytic subunit. Brm and BRG1 do not function identically, so this complex can regulate gene expression either positively or negatively, depending on the promoter to which it is recruited. Notably, Brm attenuation due to posttranscription suppression occurs often in human tumor cells, in which this event contributes to their oncogenic potential. Here, we report that the 3 0 -untranslated re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 39 publications
4
99
1
Order By: Relevance
“…Previous studies demonstrated that miR199a-5p transcription was activated by Egr1 and Twist1, two transcription factors that are modestly expressed in myogenic progenitors, but are expressed at low levels in differentiated MT. 20,21 However, miR-199a-5p expression levels are the highest in MT, which suggests that a transcriptional activator of miR-199a-5p expression might also increase during myogenic differentiation. In support of this hypothesis, SRF and its transcriptional cofactors MRTF (myocardin-related transcription factor)-A and MRTF-B, have been shown to increase in expression levels during myogenic [24][25][26] Based on evolutionary conservation, we generated several luciferase reporter constructs (2, 1, 0.8, 0.5, and 0.2 kb) using DNA sequences upstream of the miR-199a-2 locus that contained either the SRF CArG box (labeled S1 or S2 for Site 1 or Site 2, respectively) along with a conserved E-box site to which the myogenic helix-loop-helix factors could potentially bind (Figures 2a and b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that miR199a-5p transcription was activated by Egr1 and Twist1, two transcription factors that are modestly expressed in myogenic progenitors, but are expressed at low levels in differentiated MT. 20,21 However, miR-199a-5p expression levels are the highest in MT, which suggests that a transcriptional activator of miR-199a-5p expression might also increase during myogenic differentiation. In support of this hypothesis, SRF and its transcriptional cofactors MRTF (myocardin-related transcription factor)-A and MRTF-B, have been shown to increase in expression levels during myogenic [24][25][26] Based on evolutionary conservation, we generated several luciferase reporter constructs (2, 1, 0.8, 0.5, and 0.2 kb) using DNA sequences upstream of the miR-199a-2 locus that contained either the SRF CArG box (labeled S1 or S2 for Site 1 or Site 2, respectively) along with a conserved E-box site to which the myogenic helix-loop-helix factors could potentially bind (Figures 2a and b).…”
Section: Resultsmentioning
confidence: 99%
“…12,21,40 Another recent study showed that miR-199a-5p expression was upregulated in mice with idiopathic pulmonary fibrosis (IPF), suggesting that miR-199a-5p could regulate tissue fibrosis in different types of fibroproliferative diseases. 41 MiR-199a-5p can also regulate cardiomyocyte size during cardiac hypertrophy under ischemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…23 Because Twist1 is decreasingly expressed and decreasingly interacts with DNM3os during HSC activation, 23 this causes activation-associated decreases in expression of miR-214 23 or miR-199a-5p (these results), thereby allowing expression of their common CCN2 target and its downstream fibrogenic mediators (a-SMA, collagen). Future studies will investigate other control mechanisms of the miR-199a-5p/miR-214-CCN2 axis in activated HSCs, including transcriptional regulation of miR-199a-2 by Egr-1 and STAT3 transcription factors 55,56 and methylation or histone modifications of miR-199a-2 or miR-199a-1, 57e59 the latter of which is a separate precursor of miR-199a-5p that is not regulated by Twist1 or Egr-1. 42 Exosomes are membranous nanovesicles that arise by inward budding of multivesicular bodies, which then fuse with the plasma membrane and cause exosomes to be released from the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transfection with a miR-155 inhibitor increased the percentage of cells in the G1 phase, suggesting that low expression of miR-155 induced G1-phase cell cycle arrest (27). The targets of miR-199a, V-Ki-Ras2 Kirsten rat sarcoma viral oncogene homolog and mitogen-activated protein kinase kinase 4 have been identified (28)(29)(30)(31), and the inhibitory effects of miR-199a and/or miR-214 on the expression of these target genes have been demonstrated (31). miR-199a and miR-214 may have important roles in cell growth and proliferation via the mitogen-activated protein kinase pathway (31,32).…”
Section: Discussionmentioning
confidence: 99%